Synthesis, Structural Characterization, and Catalytic Property of A Zn(II) Complex with 5-Bromosalicylaldehyde Ligand - Xi Shi Tai; Peng Fei Li; Xin Wang; Li Li Liu (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The study on catalytic activity of complex materials has been one of the hot spots in coordination  chemistry. In order to extensively study the catalytic activity of complexes, a new six-coordination Zn(II) complex material, [ZnL2(H2O)2] (C1) (HL = 5-bromosalicylaldehyde), has been prepared with 5-bromosalicylaldehyde, NaOH, and Zn(CH3COO)2·2H2O as raw materials. The structure of C1 was determined by elemental analysis, IR spectra, and single crystal X-ray diffraction. The Zn(II) complex shows a moderate catalytic activity for A3 coupling reaction of benzaldehyde, piperidine, and phenylacetylene with the benzaldehyde conversion reached 54.6 %. Furthermore, the Zn(II) complex catalyst exhibited 54.8 %, 53.8 %, and 54.4 % conversions of benzaldehyde in the second, third, and fourth cycles, respectively.  In addition, the Zn(II) complex features a selectivity of 100 % to the     product of propargylamine for the A3 coupling reaction.